SURVEI KEMAMPUAN DAN KETERAMPILAN MOTORIK DASAR LOKOMOTOR SISWA KELAS IV SD NEGERI 161/IX PANCA MULYA - Ananda Ponsyah; Atri Widowati; Adhe Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of basic locomotor motor skills in running and jumping among fourth-grade students at SD Negeri 161/IX Panca Mulya. The population in this study was all fourth-grade students at SD Negeri 161/IX Panca Mulya in the 2025/2026 academic year. The sample in this study was the entire population, so the technique used was total sampling. Thus, the sample size in this study was 33 students, equal to the population size, consisting of 23 female students and 10 male students. This study used a descriptive method with a survey approach. This study used a descriptive survey research design with a cross-sectional model. The data obtained in this study consisted of test data (basic locomotor motor skills) and non-test data (basic locomotor motor skills). Therefore, data analysis was carried out using two approaches, namely Test Data Analysis (Zig-Zag Running and Long Jump Without Run-up Motor Skills) and Non-Test Data Analysis (Running and Jumping Skills Rubric). Based on the results of the study, it can be concluded that the fourth-grade students of SD Negeri 161/IX Panca Mulya have overall basic locomotor motor skills in the Good category, namely 11 students (33%), followed by the Moderate category with 10 students (30%), Poor with 7 students (21%), Very Poor 4 students (12%), and Very Good 1 student (3%). Meanwhile, the overall results of students' basic locomotor motor skills were also in the Good category, namely 16 students (48.48%), followed by the Moderate category with 15 students (45.45%), and Poor with 2 students (6.06%). These results indicate that, overall, students' mastery of basic locomotor motor skills has been well established, with a predominance of the Good category, although there are still students in the Moderate and Poor categories who require additional guidance to improve their movement skills.